Use of tocopherol extract and different nitrite sources and starter cultures in the production of organic botifarra catalana, a cooked cured sausage. (April 2016) - Magrinyà, Núria; Bou, Ricard; Rius, Núria; Codony, Rafael; Guardiola, Francesc
This research evaluates the effects of adding a tocopherol mix (0 or 200 mg/kg), two nitrite sources (sodium nitrite or a nitrate-rich vegetable concentrate) and the use of Staphylococcus carnosus together with fermentation types that varied in temperature (12 h at 4 ℃ or 16 ℃) on different quality parameters and acceptability of cooked cured sausages after vacuum packing and storage at 4 ℃ for 120 days. In the presence of S. carnosus, residual nitrate and nitrite levels were reduced. Sausages containing vegetable concentrates and without S. carnosus resulted in higher amounts of residual nitrate and lower curing efficiency. The lowest values in redness and acceptability were observed in those sausages without starter cultures. The addition of tocopherols had no effect on oxidative status and susceptibility to oxidation. However, the highest amount of hydroperoxides was related with nitrite decreased formation. Overall, vegetable concentrates can be used as curing agents if fermentation with a nitrate-reducing starter culture is allowed.